Ketahanan Korosi Baja Ringan di Lingkungan Air Laut - Andreas Surjaka Ispandriatno; Radhian Krisnaputra (Jurnal Material Teknologi Proses: Warta Kemajuan Bidang Material Teknik Teknologi Proses, 2016)
The development of the materials for construction more rapidly. It is characterized by the increasing number of manufacturers that produce materials that has the same strength, but with a lighter weight and better durable. One ingredient that is getting a lot of use is light-weight steel. This research aims to determine the resistance of light-weight steel corrosion surrounding sea water. The testing is done by taking a light-weight steel 3 different brands, then testing to determine the layer thickness zincalume each brand. Further corrosion testing with a variety of media corrosion from seawater from three different sources, from North sea of Indonesia represented by the West Coast of Aceh, from South of Java Island represented Samas Beach, and from North of Java island represented Port of Tanjung Mas Semarang with sea water content variation dilution 10x, 50xand 100x. The results show that the condition of sea water from 3 sources test results showed no difference in the rate of mild steel corrosion layer zincalume meaning. Zincalume coated with 10 micron layer can improve the corrosion resistance of light-weight steel in sea water environments up to 4.9 compared without coating. Three brands mild steel A, B and C with zincalume layer thickness between 10 to 20 microns did not show differences in the corrosion rate of light-weight steel which means at various concentrations of sea water dilution.